Multiply both sides by <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Simplify the left side.

Simplify <math><mstyle displaystyle="true"><mrow><mo>(</mo><mfrac><mrow><mn>7</mn><mi>x</mi></mrow><mrow><mn>6</mn></mrow></mfrac><mo>-</mo><mn>3</mn><mo>)</mo></mrow><mo>⋅</mo><mn>4</mn></mstyle></math> .

Apply the distributive property.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Combine <math><mstyle displaystyle="true"><mfrac><mrow><mn>7</mn><mi>x</mi></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Multiply.

Multiply <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Simplify the right side.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Move all terms containing <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> to the left side of the equation.

Subtract <math><mstyle displaystyle="true"><mn>5</mn><mi>x</mi></mstyle></math> from both sides of the equation.

To write <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn><mi>x</mi></mstyle></math> as a fraction with a common denominator, multiply by <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn><mi>x</mi></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> .

Combine the numerators over the common denominator.

Simplify each term.

Simplify the numerator.

Factor <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> out of <math><mstyle displaystyle="true"><mn>14</mn><mi>x</mi><mo>-</mo><mn>5</mn><mi>x</mi><mo>⋅</mo><mn>3</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> out of <math><mstyle displaystyle="true"><mn>14</mn><mi>x</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> out of <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn><mi>x</mi><mo>⋅</mo><mn>3</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> out of <math><mstyle displaystyle="true"><mi>x</mi><mo>⋅</mo><mn>14</mn><mo>+</mo><mi>x</mi><mrow><mo>(</mo><mo>-</mo><mn>5</mn><mo>⋅</mo><mn>3</mn><mo>)</mo></mrow></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>15</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>14</mn></mstyle></math> .

Move <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> to the left of <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Move the negative in front of the fraction.

Add <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> to both sides of the equation.

Multiply both sides of the equation by <math><mstyle displaystyle="true"><mo>-</mo><mn>3</mn></mstyle></math> .

Simplify both sides of the equation.

Simplify the left side.

Simplify <math><mstyle displaystyle="true"><mo>-</mo><mn>3</mn><mrow><mo>(</mo><mo>-</mo><mfrac><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></mfrac><mo>)</mo></mrow></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Move the leading negative in <math><mstyle displaystyle="true"><mo>-</mo><mfrac><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> into the numerator.

Factor <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mo>-</mo><mn>3</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Multiply.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>12</mn></mstyle></math> .

Do you know how to Solve for x (7x)/6-3=(5x)/4? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.